PENGARUH PENGGUNAAN PERPUSTAKAAN DIGITAL TERHADAP PENINGKATAN KINERJA BELAJAR MAHASISWA DI SEKOLAH PASCASARJANA UNIPA SURABAYA - Wawan Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of digital library use on improving student learning performance at the UNIPA Surabaya Graduate School. The use of digital libraries is increasingly important in supporting the teaching and learning process, particularly in providing easy and fast access to various academic resources. The method used in this study is regression analysis, which measures the effect of digital library use on student learning performance. The results of the analysis indicate that digital library use has a positive and significant effect on improving student learning performance. The regression coefficient indicates that each one-unit increase in digital library use increases student learning performance by 0.575. Furthermore, the results of the significance test indicate that the effect of digital library use is highly significant with a Sig. value of 0.000. Based on these findings, it can be concluded that digital library use plays a significant role in supporting the improvement of student academic performance.